The Discovery Learning Model in Inclusive Education to Foster Tolerance at Pondok Modern Darussalam Gontor - Syarifah, Syarifah; Mistar, Junaidi; Ahmadan, Madani; Maskuri, Maskuri (Jurnal Penelitian Pendidikan, 2025)
This study aims to examine the implementation of the Discovery Learning model in inclusive education to foster tolerance at Pondok Modern Darussalam Gontor, a pesantren known for the diversity of its students’ backgrounds. The background of this research is based on the importance of creating an inclusive and harmonious learning environment amid the cultural, ethnic, and socioeconomic plurality of the students. The research employs a qualitative approach using the ethnographic method, involving field observations, unstructured interviews, and documentation conducted over the course of one year within the environment of Pondok Modern Darussalam Gontor. The findings indicate that tolerance education at Gontor is implemented through two models: the direct model, which emphasizes social interaction among student groups, and the indirect model, which focuses on developing open-minded personalities toward differences. The Discovery Learning model is applied in various learning activities, where students are encouraged to actively explore, discover, and collaboratively solve problems. This process not only enhances students’ cognitive and spiritual abilities but also cultivates mutual respect and tolerance, both in passive and active forms. The study concludes that the application of the Discovery Learning model in inclusive education at Pondok Modern Darussalam Gontor is effective in shaping students’ tolerance attitudes and contributes significantly to the development of character education models in Islamic boarding schools and other educational institutions in Indonesia.